High temperature effects on fatigue performance and crack initiation mechanisms of 316LN stainless steel for nuclear power pipelines - JianNeng Zheng; JunChao Hu; YueHui Jiang; QingYuan Wang; Kun Yang (Journal of Materials Research and Technology)
This study performed high-cycle fatigue tests on 316LN stainless steel (SS) for nuclear power application to evaluate its fatigue behavior at both room temperature (RT) and 350 °C. Moreover, its microstructural features and fatigue crack nucleation mechanisms were further studied. It was found that fatigue crack initiation predominantly occurs at the SS specimen surface. At RT, microcrack initiation modes include both transgranular and intragranular mechanisms, with the {100} slip plane contributing to crack initiation alongside the preferential {111} slip plane. At 350 °C, the crack initiation mode shifts primarily to intragranular mechanisms, with active slip planes identified as {111} and {110}.